A New Secret Sharing Scheme With Priority in Order of Sharing and its Application in Multi Authority E-voting Systems - Mousavi, Seyyed Hamed; Rahimi, Saeed; Alsaadi, Mousa Javidi; Mousavi, Foroogh (Ciência e Natura, 2015)
Secret sharing caused a high level of security in encrypted systems. So, there are wide ranges of methods based on the secret sharing policies. Secret sharing schemes has 2 main aims. The first is determined to decrease the risks of attacks by adversaries which can be done by increasing the number of authorities. Second is to remove the dependence of protocol to an special part.In this paper, the priority of parties to share the secret is important. Also different authorities may be given different type of part. We also propose some voting systems in order to justify suggested secret sharing protocol. Also we analyze theses protocols to show that this secret sharing protocol saves the security of E-voting system.